ANALISIS DETERMINAN CADANGAN DEVISA DI INDONESIA - Yunella Safitri; Dewi Zaini Putri (Universitas Negeri Padang, 2021)
This study examines the analysis of the determinants of Indonesia's foreignexchange reserves. The data used in this study is secondary data obtained from the publications of the relevant agencies. This study uses Multiple Linear Regression analysis. The results of the study: (1) The effect of exports on foreign exchange reserves is insignificant and positive (2) The effect of imports on foreign exchange reserves is positive and not significant, (3) The effect of the exchange rate on foreign exchange reserves is significant and positive, (4) The effect of interest rates to foreign exchange reserves is significant and negative, (5) Simultaneously, the effect of exports, imports, exchange rates and interest rates on Indonesia's foreign exchange reserves is significant